Small RNA Regulation of Virulence in Pathogenic Escherichia coli - Sy, Brandon M.; Tree, Jai J. (Frontiers in Cellular and Infection Microbiology, 2021)
Enteric and extraintestinal pathotypes of Escherichia coli utilize a wide range of virulence factors to colonize niches within the human body. During infection, virulence factors such as adhesins, secretions systems, or toxins require precise regulation and coordination to ensure appropriate expression. Additionally, the bacteria navigate rapidly changing environments with fluctuations in pH, temperature, and nutrient levels. Enteric pathogens utilize sophisticated, interleaved systems of transcriptional and post-transcriptional regulation to sense and respond to these changes and modulate virulence gene expression. Regulatory small RNAs and RNA-binding proteins play critical roles in the post-transcriptional regulation of virulence. In this review we discuss how the mosaic genomes of Escherichia coli pathotypes utilize small RNA regulation to adapt to their niche and become successful human pathogens.